PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN TIDAK TETAP DI PT INDO HUSADA UTAMA - Ranti Emisa; Andi Heru Susanto (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
Background: The current phenomenon in the world of work is a decrease in employee loyalty caused by several factors. This study aims to determine the effect of compensation and work environment on employee loyalty. Design / method / approach: In this study using associative quantitative research methods with a sample of 275 respondents. The instrument used was a questionnaire containing 41 questions. Instrument testing uses validity and reliability tests, and hypothesis testing uses multiple linear regression analysis. Results: The results of this study show that compensation does not have a positive and significant effect on employee loyalty, the work environment has a positive and significant effect on employee loyalty and compensation and loyalty simultaneously have a positive and significant effect on employee loyalty.